Comparison of the Expression Intensity of Estrogen Receptor Marker in Oral and Cutaneous Pemphigus Vulgaris - S Rahrotaban; S Samani; M Jolehar; F Badie (Islamic Azad University, 2017)
Background and aim: Pemphigus vulgaris (PV) is an autoimmune disorder that can clinically manifest as oral mucosal ulcers. Several researchers believe that the level of female sex hormones such as estrogen and progesterone could be effective in the pathogenesis and growth of lesions such as desquamative gingivitis. Studies related to oral ulcers have revealed contradictory results regarding the presence of estrogen in the gingiva and salivary glands. Therefore, the main objective of this research was the evaluation and comparison of estrogen receptor (ER) expression in oral and cutaneous PV. Materials and Methods: In this cross-sectional study, immunohistochemical staining was performed on 40 Paraffin blocks of oral and cutaneous PV. Staining intensity was investigated. Data were analyzed by Mann-Whitney test, Fisher test and T-test using SPSS 18 software. Results: The mean age of the patients equaled 38.3±11.8 and 42.8±11.3 years in oral and cutaneous PV, respectively. The most common sites of ER expression were the buccal mucosa (55%), trunk (21.1%) and scalp (21.1%). Positive ER expression in oral and cutaneous PV was found in 35% and 89.4% of the cases, respectively. Also, there were significant differences in ER expression intensity between cutaneous and mucosal PV (P=0.001). There was no significant correlation between sex, age and ER expression in cutaneous and oral PV Conclusion: The results of the present study showed that there were significant differences in the intensity of ER expression between cutaneous and mucosal PV.